Retracted: how to solve the moral dilemma of helping a fallen old man: an economic point of view - Li, Fengsen (Business, Management and Economics Engineering, 2013)
Retracted: how to solve the moral dilemma of helping a fallen old man: an economic point of view.[Business, Management and Education 11(2):209-223, 2013]